Genius culture: how we influence student identity in STEM - Bowman, Larry L. (Frontiers in Education, 2023)
In STEM, identity and belonging are affected by how students view themselves as belonging in STEM or not. The movement to help students understand that anyone can be successful in STEM is an incredibly important one. However, how students construct their identities within STEM is important for maintaining their engagement within STEM fields over time. If we condition students to expect positive feedback for having an aptitude in a STEM field early-on, what I deem ‘genius culture,’ we risk helping these develop resilience when faced with challenges. Although, if we tell students that everyone can succeed in STEM, we risk deflating students who are gifted or talented in STEM and equating growth/improvement as mastery, thereby discouraging inquiry. Moreover, as instructors, our own sense of STEM-self affects how we teach and reward our students for their successes. A more sustainable goal is to make students aware of their STEM-self and help students bolster their sense of belonging in STEM rather than acknowledging only their perceived successes or failures.